The Effect of the Demonstration Education Method Using Short Education Movie (SEM) on Knowledge and Attitudes about Mild Wound Care in Children - Susanti Widiastuti; Rizki Nursasmita; Adinda Wardani (KHD Production, 2026)
Children exhibit a range of individual characteristics, such as age, cognitive development, emotional maturity, and prior experiences, that significantly influence how they understand and respond to wound care. These differences shape both their knowledge of appropriate first-aid practices and their attitudes toward managing injuries, leading to varied approaches in caring for wounds when they occur. This study's Objective is to analyze the effect of the demonstration education method using Short Education Movie (SEM) on children's knowledge and attitudes toward wounds. A quasi-experimental study using a pretest-posttest control group design with a total sampling technique involving 152 students from Baktijaya 05 Elementary School, Depok. A questionnaire was used to assess knowledge and attitudes toward wound care, along with a Short Education Movie (SEM) media. Data analysis used the Wilcoxon Signed-Level Test. There was a significant difference between the pre- and post-intervention knowledge scores, indicating that the intervention successfully improved respondents' knowledge (p=0.0001). There is a significant difference between the before and after Attitude intervention, indicating that the intervention successfully improved Attitude (p=0.0001). Health education using the demonstration method, combined with the Short Education Movie (SEM), significantly improved knowledge and attitudes toward minor wound care among school-age children.